A class of N-player Colonel Blotto games with multidimensional private information - Christian Ewerhart; Daniel J. Kovenock (University of Zurich, Department of Economics, 2021)
In this paper, we study N-player Colonel Blotto games with incomplete information about battlefield valuations. Such games arise in job markets, research and development, electoral competition, security analysis, and conflict resolution. For M Ï N + 1 battlefields, we identify a Bayes-Nash equilibrium in which the resource allocation to a given battlefield is strictly monotone in the valuation of that battlefield. We also explore extensions such as heterogeneous budgets, the case M È N, full-support type distributions, and network games.
Keywords: C72; D72; D82; 330; Colonel Blotto games; private information; Bayes-Nash equilibrium; generalized Dirichlet distributions; networks; Netzwerk; Nash-Gleichgewicht; Ressourcenallokation